Ալեքսանդրապոլի գրական-երաժշտական բարքերի արտացոլումը «Սոխակ Հայաստանի» երգարանում - Այվազյան, Գևորգ; Հայրապետյան, Սերգո
Արևելահայ գավառակենտրոն Ալեքսանդրապոլի հասարակական միտքն անընդհատ արտահայտվելու հնարավորություններ է փնտրել: 1870-ական թթ. այդպիսի հրաշալի առիթ է հանդիսացել Բաքվում «Սոխակ Հայաստանի» լիակատար երգարանի հրատարակումը: Ժողովածուն գրավել է ալեքպոլցի կրթամշակութային առանցքային որոշ գործիչների ստեղծագործական ուշադրությունը: Նրանք այդտեղ զետեղել են իրենց սոցիալ-քաղաքական բնութագծերով գրվածքները: Накануне русско-турецкой войны 1877-1878 гг. литературно-общественные деятели Ширакской области питали надежды на Возрождение Армении. Они искали подходящие формы выражения своих благородных намерений. Это идеологическая группировка для реализации общеполезных проектов воспользовалась возможностями издания воспитанника Общества Человеколюбия в Баку Авака Григорьева, с символическим именем «Соловей Армении». Во всех томах песенника напечатаны или переизданы песни, написанные на стихи разночинной интеллигенции Александрополя. Авторы композиции с лёгким шёпотом размышляли о вопросе статуса автономии Западной Армении, о нравственных проблемах общества и о целенаправлении процесса воспитания и обучения. On the eve of the Russian-Turkish war of 1877-1878 literary and public figures of the Shirak region harbored hopes for the revival of Armenia. They looked for suitable forms of expression of their noble intentions. This ideological group, for the implementation of generally useful projects, took advantage of the publication of Avag Grigoryants, a pupil of the Society for Humanity in Baku, with the symbolic name "The Nightingale of Armenia". In all volumes of the songbook, songs written to the verses of the various intelligentsia of Alexandrapol are printed or republished. The authors of the composition with a light whisper pondered the issue of the autonomy status of Western Armenia, the moral problems of society and the purposefulness of the process of education and training.
Keywords: Գրականություն